Role of blood transfusion in saving mothers - Mohi, Manjit K.; Aggarwal, Sangeeta; Khurana, Satinder Pal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Blood transfusion is recognised as one of the eight essential components of the comprehensive emergency obstetric care module which has been designed to reduce maternal morbidity and mortality rates after major obstetric hemorrhage and anemia. Methods: This is a prospective observational study conducted between April1, 2016 to September 30, 2018 in department of obstetrics and gynecology, Government Medical College, Patiala. The MNM cases given transfusion were analysed in respect of number of antenatal visits, type of admission, distance of place of first referral unit from tertiary health care facility, amount of blood transfused, indications of blood transfusion, causes of haemorrhage and intervention performed. Results: During this period, there were 123 cases of MNM, 90 patients required blood transfusion and were considered in this study. Maximum number of cases (94.45%) were between 20-35 years of age. Majority of cases were primipara (52.22%). 47.77% cases were in 3rd trimester, 33.33% postnatal cases and 16.66% cases were in first trimester. 88.88% cases requiring transfusion belong to low socioeconomic status. There was no antenatal visit in 80% cases who required blood transfusion. 78.8% patients required more than 4packed red cell transfusions. Haemorrhage was the indication in 60% cases for blood transfusion and anaemia in 40% cases. Postpartum haemorrhage (28.4%) was most common indication for blood transfusion followed by ruptured ectopic pregnancy (27.77%), antepartum haemorrhage (11.11%), rupture uterus (7.4%), rectus sheath hematoma (5.55%), placenta accreta (5.55%) and inversion uterus (3.7%). Surgical interventions were performed in 51 cases. Conclusions: Prevention and timely treatment of anaemia must receive attention by more active participation in term of antenatal check-ups. Skilled management of patients at the first referral units is advocated. There should be familiarity with the local protocol of relevant members of staff for management of massive hemorrhage. All major hemorrhages should be reviewed to ensure that there is no delay in provision of blood products.